THE DYNAMICS OF SUICIDES AS AN INDICATOR OF THE SOCIO-ECONOMIC PROBLEMS OF THE MODERN VILLAGE OF CHINA - Baynova, Maria; Shasha , In; Kozyrev , Maxim; Petrov , Alexander; Sulyagina , Julia (Revista Inclusiones, 2020)
The article is devoted to modern research in the field of rural sociology in modern China. Existing studies of the Chinese village are limited by the interest mainly to the economic changes. However, social changes are not less importance, especially in light of the proclamation of the need to build a “harmonious socialist society” in the PRC. The development of market-based economic relations and rapid urbanization have significantly changed the Chinese village for the last thirty years of the implementation of the policy of reforms and openness.The problems that the Chinese sociologists use the integral concept of “Sannun” (三农) (including the triple problems of rural development, agriculture and the peasants themselves) have become increasingly acute. In connection with the escalation of negative processes, the Government of the People’s Republic of China has initiated a series of political initiatives aimed at modernizing agriculture and socio-economic integration of the city and the village.